Frequencies of the T-455C and C-482T apoCIII gene polymorphisms in different South African population groups and their relationship to fasting serum triglyceride levels - Naran, N.H.; Raal, F.J.; Crowther, N.J. (SA Heart Journal, 2017)
Studies have demonstrated that serum triglyceride levels are higher in Indian and White than Black South African subjects. Polymorphisms in the apoCIII gene have been associated with raised triglyceride levels. This study investigated the prevalence of apoCIII polymorphisms and their effect on triglyceride levels in three South African population groups and in subjects with fasting hypertriglyceridaemia (HT). Two apoCIII polymorphic sites (T-455C and C-482T) were studied in 78 European, 24 Indian and 25 African subjects. Each ethnic group included HT and non-HT (control) patients. Although triglyceride levels were much higher in the HT subjects, no significant differences were noted between the groups for allele or genotype frequencies at either apoCIII locus. Furthermore, at neither locus was there an association between the genotype and serum triglyceride levels. The HT and control subjects were therefore combined and ethnic differences in allele frequencies were investigated. The African subjects had a higher frequency (0.79) of the unfavourable C allele at position 455 than both Indian (0.56; p‹0.05) and European (0.41; p‹0.0005) subjects. Furthermore, African subjects had a higher frequency (0.77) of the unfavourable T allele at locus 482 than Indian (0.44, p‹0.005) and European (0.36, p‹0.0005) subjects despite triglyceride levels being lower in the African (0.60 [1.60] mmol/l) than European (0.90 [0.40] mmol/l; p‹0.05) control subjects. These results suggest that the apoCIII polymorphisms studied do not contribute to the raised triglyceride levels in HT subjects and do not explain the ethnic differences observed in fasting serum triglyceride levels.